Immune Modulation by Human Secreted RNases at the Extracellular Space - Lu, Lu; Li, Jiarui; Moussaoui, Mohammed; Boix, Ester (Frontiers in Immunology, 2018)
The ribonuclease A superfamily is a vertebrate-specific family of proteins that encompasses eight functional members in humans. The proteins are secreted by diverse innate immune cells, from blood cells to epithelial cells and their levels in our body fluids correlate with infection and inflammation processes. Recent studies ascribe a prominent role to secretory RNases in the extracellular space. Extracellular RNases endowed with immuno-modulatory and antimicrobial properties can participate in a wide variety of host defense tasks, from performing cellular housekeeping to maintaining body fluid sterility. Their expression and secretion are induced in response to a variety of injury stimuli. The secreted proteins can target damaged cells and facilitate their removal from the focus of infection or inflammation. Following tissue damage, RNases can participate in clearing RNA from cellular debris or work as signaling molecules to regulate the host response and contribute to tissue remodeling and repair. We provide here an overall perspective on the current knowledge of human RNases’ biological properties and their role in health and disease. The review also includes a brief description of other vertebrate family members and unrelated extracellular RNases that share common mechanisms of action. A better knowledge of RNase mechanism of actions and an understanding of their physiological roles should facilitate the development of novel therapeutics.